2005
DOI: 10.1021/ol050617r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nucleoside α-Thiotriphosphates via an Oxathiaphospholane Approach

Abstract: [reaction: see text]. Nucleoside 5'-O-(alpha-thiotriphosphates) were obtained in reactions of the appropriate nucleoside 5'-O-(2-thio-1,3,2-oxathiaphospholanes) with pyrophosphate in the presence of DBU. The presented method allows also for preparation of alpha-seleno congeners and corresponding alpha-modified diphosphates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Pathway B was excluded as nucleoside 5'- O -(1-thiodiphsophates) can be obtained by procedures similar to those for 5'- O -(1-thiotriphosphates), however, with lower yields 28,45. Moreover, nucleoside diphosphates are available from corresponding activated monophosphates used in pathway A.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway B was excluded as nucleoside 5'- O -(1-thiodiphsophates) can be obtained by procedures similar to those for 5'- O -(1-thiotriphosphates), however, with lower yields 28,45. Moreover, nucleoside diphosphates are available from corresponding activated monophosphates used in pathway A.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine 5Ј-(␣-thio)triphosphate (ATP(S) and cytidine 5Ј-(␣-thio)triphosphate (CTP␣S) were obtained as the S P isomers after enzymatic phosphorylation of AMPS and CMPS by adenylate and pyruvate kinases (Connolly et al, 1984;Koziolkiewicz et al, 2002). Deoxyadenosine 5Ј-(␣-thio)triphosphate (dATP␣S) was synthesized as a mixture of diastereomers (Misiura et al, 2005), which were separated using high-performance liquid chromatography (HPLC; an ODS Hypersil column, 4.6 ϫ 260 mm) using a linear gradient of 0-10% CH 3 CN/0.1 M triethyl ammonium bicarbonate (TEAB) pH 7.4, 0.33%/minute at a flow rate 1 mL/min. The retention times for the S P and R P isomers were 20.85 and 21.85 minutes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For more detailed analysis of the inhibitory effect observed for nucleside (␣-thio)triphosphates, we carried out additional experiments using the R P and S P diastereomers synthesized by the oxathiaphospholane method (Misiura et al, 2005). Inhibitory effects of the dATP␣S diastereomers expressed as their IC 50 values are presented in Table 5.…”
Section: Limited Diastereoselectivity Of Datp␣s Inhibitorsmentioning
confidence: 99%
“…16,17 On the other hand, because chromatographic separation of nucleoside-5 0 -O-oxathiaphospholane monomers, carrying typical protecting groups at the 3 0 -or 2 0 -and 3 0 -hydroxyl functions, could not be achieved, numerous P-chiral biophosphates were synthesized using unresolved monomers (e.g., 8, Scheme 3). [18][19][20] Here, we report on the synthesis of selected 3 0 -O-acylated deoxyribonucleoside-and 2 0 ,…”
Section: Nucleosidementioning
confidence: 99%
“…29 As mentioned in the Introduction, NDPs and NTPs are biologically important compounds and their diastereomerically pure P-chiral analogs are useful tools in biochemi-cal studies. Our earlier experiments 18 showed that 3 0 -O-acetyl-thymidine-5 0 -O-(2-thio-1,3,2-oxathiaphospholane) (8, unseparated mixture of P-diastereomers) reacted with the phosphate and pyrophosphate anions to yield the corresponding 5 0 -O-(a-thiodiphosphate) (Scheme 3) and 5 0 -O-(a-thiotriphosphate), respectively.…”
Section: Opening Of the Oxathiaphospholane Ring With Anions Of Phosphmentioning
confidence: 99%